The role of community-based nursing interventions on knowledge, self-efficacy, and blood pressure control among elderly people with hypertension - Herlinah, Lily; Khasanah, Uswatul; Syamsir, Syamikar Baridwan; Badriah, Siti (Malahayati International Journal of Nursing and Health Science, 2024)
Background: The high prevalence of hypertension in the elderly has serious consequences with the potential to cause various health complications, especially negative impacts on the cardiovascular system, which can include heart failure, stroke, myocardial infarction, and even fatal risks. Community-Based Nursing Intervention (CBNI) has been identified as an effective solution in efforts to improve hypertension management in the elderly population.Purpose: To evaluate the impact of CBNI on knowledge, self-efficacy, and blood pressure values of hypertensive elderly before and after the intervention.Method: The research method used was quasi-experimental with a pre-post design without a control group. A sample of 30 participants was selected through total sampling. The measurement instruments involved the assessment of knowledge, self-efficacy, as well as blood pressure measurements. The intervention included teaching about hypertension, nutritional management, and progressive muscle relaxation therapy (PMRT) combined with music therapy. Data analysis was performed using paired t-tests.Results: The research results showed significant differences before and after the intervention in the variables of knowledge (p=0.000), self-efficacy (p=0.000), systolic blood pressure (p=0.000), and diastolic blood pressure (p=0.000).Conclusion: This study highlights the positive potential of Community-Based Nursing Intervention as an approach that can be adopted and reinforces the important role of community-based nurses in providing effective care and education for the elderly population with hypertension.